Analisis Karakteristik Sosial-Ekonomi dan Demografi terhadap Partisipasi Perempuan dalam Pasar Tenaga Kerja di Indonesia - Raihannabil, Syfriza Davies; Ghaista, Indahtul; Susiawati, Ni Luh Putu Ari; Kartiasih, Fitri (Pusat Pengembangan Kebijakan Ketenagakerjaan Kementerian Ketenagakerjaan Republik Indonesia, 2025)
Indonesia has the third lowest FLFP with the second highest gender gap in Southeast Asia in the labor market dimension despite an almost equal male and female population. This study analyzes the short-run and long-run relationship between socioeconomic and demographic characteristics on female participation in the labor market. The method used is the Error Correction Model (ECM). The results show that wage/salaried workers, female average years of schooling, and net migration have short-run and long-run effects on FLFP. Meanwhile, the unemployment rate, female participation in higher education, and child population have no impact in the short-run but have a significant effect in the long-run. The adjustment process from short-run to long-run equilibrium is 55.2% in the first year, while 44.8% in the following years has an adjustment time of 1.81 years. This study suggests the need to strengthen quality and flexible employment policies, inclusive education, and support gender-friendly policies, such as childcare services and maternity leave, to increase female participation in the labor market.